The Legal Protection for Notary Employees as Witnesses in Making and Inaugurating Deeds - Nadiyon, Nadiyon; Gunarto, Gunarto (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to find out and analyze the position of notary witnesses in making deeds and how legal protection is for notary employees as witnesses in making and formalizing deeds. This research uses normative juridical research methods. The results of the research conclude that the position of instrumental witness plays a role in witnessing 2 (two) important stages in making a deed, namely the process of reading and signing (validating or formalizing) the deed and legal protection for notary employees as witnesses in making and formalizing the deed. Legal protection is found in the Law. Law of the Republic of Indonesia Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. Keywords: Employees; Instrumental; Protection; Witnesses.